Inflammatory Pseudotumor of the Liver Complicated by Lung Necrosis and Pleural Empyema: A Case Report - Klaus Steinbrück; Marcelo Enne; Reinaldo Fernandes; Jose M. Martinho; Lúcio F. Pacheco-Moreira (Case Reports in Surgery)
Inflammatory pseudotumor of the liver (IPTL) is a rare condition, but an important differential diagnosis of hepatic space-occupying lesions. It may regress spontaneously and mimic other liver tumors. Complications are usually intrahepatic. Herein, we present a case of IPTL which developed pleural empyema and lung necrosis as an uncommon complication.